An Intrinsic Motivation Analysis of the Main Character in the Joy Movie - Aprianus Agung Empawi; Clarry Sada; Eka Fajar Rahmani (Kirana Publisher (KNPub), 2024)
Joy is a motivational movie that can inspire the audience to work hard and achieve their dreams. This research aims to analyze the intrinsic motivation of the main character in the movie, employing a descriptive-qualitative design. According to the Basic Psychology Needs Theory used in this research, intrinsic motivation is driven by three basic psychological needs: autonomy (the need to control one's own experiences and actions), competence (the need to feel effective and masterful), and relatedness (the need to feel belonging and socially connected). This research is conducted by identifying all three basic psychological needs reflected in the utterances of the main character. Using the movie and its script as primary data sources, the study employs a document analysis technique to collect the data, with an observation table as a tool for data collection and a content analysis method to interpret the data. The findings show that the main character's intrinsic motivation is certainly driven by basic psychological needs. It is revealed that the main character’s intrinsic motivation is mostly driven by the need for competence, followed by autonomy and relatedness. This research not only contributes to the understanding of basic psychological needs but also their impact on intrinsic motivation, driving individuals to accomplish their goal.